Global health issues of aflatoxins in food and agriculture: Challenges and opportunities - Perng Kuang Chang (Frontiers Research Topics, 2015)
Aflatoxins are a group of polyketide mycotoxins that are produced mainly by members of the genus Aspergillus. Production of these toxic secondary metabolites is closely related to fungal development (Keller et al., 2005; Jamali et al., 2012). Contamination of food, feed and agricultural commodities by aflatoxins poses enormous economic and serious health concerns because these chemicals are highly carcinogenic and can directly influence the structure of DNA. The resulting genetic defects can lead to fetal misdevelopment and miscarriages; aflatoxins are also known to suppress immune systems (Razzaghi-Abyaneh et al., 2013). In a global context, aflatoxin contamination is a constant concern between the 35N and 35S latitude where developing countries are mainly situated. With expanding boundaries of developing countries, aflatoxin contamination has become a persistent problem to those emerging areas (Shams-Ghahfarokhi et al., 2013). The continuing threat by aflatoxin contamination of food, feed and agricultural commodities to the world population has made aflatoxin research one of the most exciting and rapidly developing study areas of microbial toxins. The present research topic includes six review articles, three mini reviews and four original research articles. Contributors highlight current global health issues arising from aflatoxins and aflatoxigenic fungi and cover important aspects of aflatoxin research including contamination of crops, epidemiology, molecular biology and management strategies. Special attention is given to fungus-plant host interactions, biodiversity and biocontrol, sexual recombination in aflatoxigenic aspergilli, potential biomarkers for aflatoxin exposure in humans and safe storage programs.